Cinnabar mineralization in fossil small mammal remains as a consequence of diagenetic processes. (27th November 2012) - García‐Alix, Antonio; Minwer‐Barakat, Raef; Martín Suárez, Elvira; Freudenthal, Matthijs; Delgado Huertas, Antonio
Abstract : The peculiar red colour of fossil small mammal remains from a late Miocene section in southern Spain suggests an unusual diagenetic alteration. These remains have been studied by means of environmental scanning electron microscope equipped with different detectors, energy dispersive X‐ray spectroscopy and an inductively coupled plasma optical emission spectrometer. The red colour is caused by the presence of cinnabar (HgS) in the pores of the fossil bones and teeth, filling the dentinal and bone tubules and other cavities that at life were filled by organic matter. A nearby cinnabar outcrop in the metamorphic materials of Sierra Nevada is interpreted as the source of mercury. This element was mobilized by meteoric diagenesis and incorporated as cinnabar in a palustrine environment, occupying pores and cavities of mammal remains shortly after the degradation of the organic matter (post‐mortem enrichment), during the early diagenesis.